2000
DOI: 10.1038/labinvest.3780020
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Appearance of Multiple B Cell Lymphoma Types in NFS/N Mice Congenic for Ecotropic Murine Leukemia Viruses

Abstract: SUMMARY:Spontaneous lymphomas occur at high frequency in NFS.V ϩ mice, strains congenic for ecotropic murine leukemia virus (MuLV) proviral genes and expressing virus at high titer. In the present study, a total of 703 NFS.V ϩ lymphomas were studied by histopathology, immunophenotypic analysis, immunoglobulin heavy chain or T cell receptor ␤ chain rearrangements, and somatic ecotropic MuLV integrations; 90% of the lymphomas tested were of B cell lineage. Low-grade tumors included small lymphocytic, follicular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…Histologic diagnoses were made according to the Bethesda classification of mouse lymphoid neoplasms (2). Features of diffuse large B-cell centroblastic and immunoblastic lymphomas have been described (2,24). Immunohistochemical studies were done using the panel of antibodies listed in Supplementary Table S1 and procedures described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic diagnoses were made according to the Bethesda classification of mouse lymphoid neoplasms (2). Features of diffuse large B-cell centroblastic and immunoblastic lymphomas have been described (2,24). Immunohistochemical studies were done using the panel of antibodies listed in Supplementary Table S1 and procedures described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Published studies from our laboratories and others have revealed that these plasmacytomas are heterogeneous and can be divided into subtypes based on histologic features and gene expression profiles, some with human counterparts (18)(19)(20)(21)(22)(23). Here, we describe a new set of mouse plasmacytomas that developed in NFS.V + mice (24). Histologically, they comprise three subsets-low grade/plasmacytic, intermediate grade/plasmablastic, and high grade/anaplastic-that closely parallel the terminologies suggested by Bartl et al (9) for variants of human multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…NFS.V ϩ mice congenic for ecotropic MuLV induction loci from strains AKR and C58 and that develop a high incidence of B-cell lymphomas of different histological types have been described previously (11). Samples obtained at autopsy were frozen for later preparation of DNA and RNA and for histopathology.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were classified as exhibiting plasma cell abnormalities including: (i) plasmacytosis, accumulations of normal-appearing, and nondividing plasma cells; (ii) plasma cell hyperplasia (PCH), mixtures of normal and aberrant hyperchromatic, sometimes mitotically active plasma cells; (iii) microplasmacytoma (mPCT), isolated clusters of malignant plasma cells, presumptive precursors of overt PCT; (iv) PCT; and (v) anaplastic plasmacytoma (PCT-A), a mixture of immunoblasts and plasma cells with Ͼ90% of cells being immature forms of malignant plasma cells. Nonplasmacytic lymphoid neoplasms were classified as follicular B cell lymphoma (FBL) or diffuse large-cell B cell lymphoma (DLCL), using criteria described in a provisional system of nomenclature for mouse hematopoietic tumors (13,14). Avidin-biotin immunoperoxidase techniques with antisera to IgL and IgH (Southern Biotechnology Associates), B220 (CD45R) (CalTag), and CD19 and CD138 (syndecan; PharMingen) were used for the determination of Ig production and surface marker expression as described (11).…”
Section: Methodsmentioning
confidence: 99%